Chapter L'Archivio del principe di Taranto Giovanni Antonio Orsini del Balzo - Petracca, Luciana (Reti Medievali E-Book, 2021)
In recent years, historiographical reflection has devoted more and more attention to the rela- tionship between the exercise of power and the processes of production/management of doc- uments, understood as real instruments of government, capable of guaranteeing the correct functioning of the administrative apparatus of kingdoms, principalities, republics and lord- ships, more or less extensive. The essay investigates one of the most important noble archives of the fifteenth-century Southern Italy, the archive of the Prince of Taranto, Giovanni Antonio Orsini del Balzo, which over time has been invested by a vast process of dispersion. The fundamental objective is to take stock of the most consistent core of documents, coming from the principality of Taranto, and merged into the fond of the Regia Camera della Sommaria of the Archivio di Stato of Naples.